2021
DOI: 10.4204/eptcs.335.27
|View full text |Cite
|
Sign up to set email alerts
|

A Deontic Stit Logic Based on Beliefs and Expected Utility

Abstract: The formalization of action and obligation using logic languages is a topic of increasing relevance in the field of ethics for AI. Having an expressive syntactic and semantic framework to reason about agents' decisions in moral situations allows for unequivocal representations of components of behavior that are relevant when assigning blame (or praise) of outcomes to said agents. Two very important components of behavior in this respect are belief and belief-based action. In this work we present a logic of dox… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…To clarify, over the last two decades researchers have shown that one can draw bridges between stit theory and theories such as dynamic logic (Canavotto, 2020;Herzig & Lorini, 2010;Horty, 2019;van Benthem & Pacuit, 2014), coalition logic (Broersen, Herzig, & Troquard, 2006b), § 1.2. Logic-Based Formalization of Responsibility • 11 alternating-time temporal logic (Broersen, Herzig, & Troquard, 2006a), and decision-& epistemic game theory (Abarca & Broersen, 2021a;Duijf, 2018;Tamminga, 2013), among others. Consequently, one can incorporate the concepts native to these fields into stit-theoretic analyses.…”
Section: The Toolmentioning
confidence: 99%
See 4 more Smart Citations
“…To clarify, over the last two decades researchers have shown that one can draw bridges between stit theory and theories such as dynamic logic (Canavotto, 2020;Herzig & Lorini, 2010;Horty, 2019;van Benthem & Pacuit, 2014), coalition logic (Broersen, Herzig, & Troquard, 2006b), § 1.2. Logic-Based Formalization of Responsibility • 11 alternating-time temporal logic (Broersen, Herzig, & Troquard, 2006a), and decision-& epistemic game theory (Abarca & Broersen, 2021a;Duijf, 2018;Tamminga, 2013), among others. Consequently, one can incorporate the concepts native to these fields into stit-theoretic analyses.…”
Section: The Toolmentioning
confidence: 99%
“…-Chapter 3 is based on my joint work with Jan Broersen (Abarca & Broersen, 2021b). Additionally, its conclusion includes a restriction of a framework that was introduced in another article with Jan Broersen (Abarca & Broersen, 2021a).…”
Section: Sources Of the Original Materialsmentioning
confidence: 99%
See 3 more Smart Citations